Inhibiting cancer metabolism by aromatic carbohydrate amphiphiles that act as antagonists of the glucose transporter GLUT1. Issue 14 (20th March 2020) - Brito, Alexandra; Pereira, Patrícia M. R.; Soares da Costa, Diana; Reis, Rui L.; Ulijn, Rein V.; Lewis, Jason S.; Pires, Ricardo A.; Pashkuleva, Iva
Abstract : We report on aromatic N -glucosides that inhibit selectively the cancer metabolism via two coexistent mechanisms: by deprivation of the glucose uptake through blocking of GLUT1 and by formation of sequestering nanonet through biocatalytic self-assembly. Abstract : We report on aromatic N -glucosides that inhibit selectively the cancer metabolism via two coexistent mechanisms: by initial deprivation of the glucose uptake through competitive binding in the glucose binding pocket of GLUT1 and by formation of a sequestering nanoscale supramolecular network at the cell surface through localized (biocatalytic) self-assembly. We demonstrate that the expression of the cancer associated GLUT1 and alkaline phosphatase are crucial for the effectiveness of this combined approach: cancer cells that overexpress both proteins are prompter to cell death when compared to GLUT1 overexpressing cells. Overall, we showcase that the synergism between physical and biochemical deprivation of cancer metabolism is a powerful approach for development of effective anticancer therapies.